2002
DOI: 10.1007/bf02704129
|View full text |Cite
|
Sign up to set email alerts
|

Thermally induced structural changes in Nomex fibres

Abstract: Thermally aged Nomex fibres manifest several residual effects viz. reduction in X-ray crystallinity, weight loss and deterioration in tensile characteristics. Surface damages in the form of longitudinal openings, holes, material deposits etc have also been observed. Based on the data from thermally exposed fibres, the time needed for states of zero tensile strength and modulus have been predicted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 9 publications
9
32
0
Order By: Relevance
“…In contrast to this, only the broad halo was observed and PMHIA spheres were completely amorphous. Although poly(1,3-phenylene isophthalate) was also a crystalline polymer, 23,24 the PMHIA spheres lost the crystallinity owing to all meta-structure and the higher Es values.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to this, only the broad halo was observed and PMHIA spheres were completely amorphous. Although poly(1,3-phenylene isophthalate) was also a crystalline polymer, 23,24 the PMHIA spheres lost the crystallinity owing to all meta-structure and the higher Es values.…”
Section: Resultsmentioning
confidence: 99%
“…Jain and Vijayan [16] showed that the number and depth of the microgrooves on the fibres of meta-aramid specimens were a function of both temperature and duration of thermal exposure. Results indicated that the severity of thermal deterioration on a specimen surface that was exposed to 300°C for 400 h was higher than that of a surface exposed to 400°C for 2.25 h.…”
Section: Exposures To High Temperatures and Heat Fluxesmentioning
confidence: 99%
“…Jain and Vijayan [16] investigated the effect of thermal ageing on the properties of meta-aramid fibres using the X-ray diffraction method. They exposed meta-aramid specimens to temperatures of 200, 300, 350 and 400°C for durations between 0.5 and 2000 h. Before the test and at different stages of the thermal exposure, the specimens were examined to consider changes in crystallinity, surface damage, and mechanical strength.…”
mentioning
confidence: 99%
“…When the fi bers are used in high temperature environments, they are subject to shrinkage or degradation. Thermally induced structural changes in Nomex ® fi bers were investigated by X-ray diffraction, scanning electron microscopy, tensile testing, and weight change; reductions in X-ray crystallinity, weight, tensile strength, and strength at break were observed (Jain and Vijayan, 2002). The heat induced fi ber and fabric shrinkage of Nomex ® is a signifi cant problem in its use for protective clothing.…”
Section: Aramidsmentioning
confidence: 99%